ANALYSIS OF CHILDREN’S UNDERSTANDING OF ENGLISH VOCABULARY ABILITY USING FLASH CARD MEDIA - Khofifah Mitha Saviera; Maman Suryaman (Universitas Muhammadiyah Gorontalo, 2022)
English comprehension is very important because it has a positive academic impact. English language skills can be seen from 4 aspects, which can be seen from the ability to read (reading skills), ability to listen (listening skills), ability to speak (speaking skills) and ability to write (writing skills) as well as the ability to have a large number of vocabularies that a person has (vocabulary skills). One of the teacher's creative efforts in making learning interesting is to use learning media. One of them uses flash card media. This study aims to determine whether flash card media can increase students' vocabulary in elementary schools. This study uses qualitative methods, namely using case studies (observational research). The subjects of this study were 1 grade IV elementary school students.